Self-medication counseling at Muhammadiyah learning center in Kepong, Kuala Lumpur - Rossy Fadia Putry; Dias Tiara Putri Utomo; Abdul Rokhman (Universitas Muhammadiyah Magelang, 2023)
Self-medication is an effort to treat the symptoms of minor illnesses which can be performed by the community. The purpose of self-medication is to relieve symptoms of minor illnesses as well as provide first aid. Regarding the importance of self-medication, community service related to self-medication was carried out. The participants were 20 student parents of Kepong Muhammadiyah learning center, Kuala Lumpur, Malaysia. The community service was conducted on September 2, 2022 and was delivered through counseling by using PowerPoint Presentations (PPT) media. To check the participants’ understanding of self-medication materials, pretest and post-test questionnaires were distributed. The result indicated an increase in the knowledge of self-medication as it was assessed by the difference between pretest scores (78) and post-test scores (93.9). To sum up, this community service is considered successful in increasing participants’ knowledge of self-medication.